2023
DOI: 10.1159/000531509
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Retinal Microcirculation Based on the Morphology of Peripapillary Atrophy in High Myopia

Abstract: Introduction: To evaluate the retinal microvasculature of the optic nerve head and macula in high myopia (HM), investigate the association between the vascular parameters and peripapillary atrophy deformation, and assess and identify the peripapillary atrophy morphology changes during the development of HM. Methods: 167 right eyes from 167 HM patients were enrolled in this cross-sectional study. Using the optical coherence tomography angiography (OCTA) and fundus camera, we evaluated the following parameters:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The outer boundary of PPA was delineated as the visible scleral edge in color photographs, aligning with the termination of the hyperreflective region in infrared (IR) images. Based on size and morphological features, a succinct classification scheme, including temporal PPA (confined to the temporal aspect of the optic disk), advanced PPA (extending to both superior and inferior aspects of the optic disk), and annular PPA (encompassing the entire peripapillary region), is introduced to intuitively indicate the severity of myopia ( 15 ). Lu et al developed a computer-aided measuring tool, enabling the quantification of PPA size on two-dimensional fundus images, marking the first instance of such quantification ( 16 ).…”
Section: Optic Disk Morphologic Abnormalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The outer boundary of PPA was delineated as the visible scleral edge in color photographs, aligning with the termination of the hyperreflective region in infrared (IR) images. Based on size and morphological features, a succinct classification scheme, including temporal PPA (confined to the temporal aspect of the optic disk), advanced PPA (extending to both superior and inferior aspects of the optic disk), and annular PPA (encompassing the entire peripapillary region), is introduced to intuitively indicate the severity of myopia ( 15 ). Lu et al developed a computer-aided measuring tool, enabling the quantification of PPA size on two-dimensional fundus images, marking the first instance of such quantification ( 16 ).…”
Section: Optic Disk Morphologic Abnormalitymentioning
confidence: 99%
“…OCTA enables the exploration of choroidal microcirculation features within PPA. Tang et al observed a reduction in peripapillary vessel density (PVD) in patients’ eyes, notably in the superior nasal (SN), nasal superior (NS), nasal inferior (NI), inferior temporal (IT), temporal inferior (TI), and superior temporal (ST) directions, accompanied by a significant expansion of PPA area ( 15 ). The OCTA choroid map delineated a localized microvasculature dropout (MvD) within the beta zone-PPA region, consistent with hypofluorescence observed in indocyanine green angiography (ICGA) ( 22 ).…”
Section: Optic Disk Morphologic Abnormalitymentioning
confidence: 99%